El devenir del testimonio: memoria y autoficción en Diario de una princesa montonera. 110% verdad (2021) de Mariana Eva Perez. (El Hilo de la Fabula, 2021)
This article aims to analyse the intersections between «memory», «testimony» and «autofiction» in Diario de una Princesa Montonera. 110% verdad (2021) by Mariana Eva Perez. The displacement implied from the concept of «truth» to the testimonial «authenticity» inaugurates, in Latin America, an ethic reconfiguration, in which the value resides now in a formal, perceptual option which upsets the categories of «fiction» and «testimony». Unclassifiable in its genre (a diary), it explores the politics of the memory of the last military dictatorship in Argentina (1976–1983) in an ironic way. The Montonero Princess, an autofictional character, parodizes the institutional strategies of reconstruction of the past, in conflict with a «culture of memory» (Huyssen, 2007).
Keywords: Memory; Autofiction; Testimony; Dictatorship